The effect of end group and graphene on dielectric properties and thermal degradation of poly(benzyl methacrylate) prepared by ATRP method - Demirelli, Kadir; Abubakar, Abdullahi Musa; Ahmad, Abdulhaleem Abdulkareem; Bagci, Eyup (Springer, 2023)
The polymer composites were prepared based on the incorporation of graphene particles in various ratios to lacton ended poly(benzyl methacrylate) (LE-PBMA). The thermal caharacterization of composites was performed by DSC and TGA techniques. The dielectric constant (epsilon '), the dielectric loss factor (epsilon '') and the ac and dc conductivities (sigma(ac) and sigma(dc)) were measured using an impedance analyzer in a frequency range from 100 to 2 kHz. The thermal degradation up to 500 degrees C under vacuum of LE-PBMA loaded with 12 w% graphene was investigated. Thermal degradation was carried out to known if the addition of graphene causes any changes in the degradation processes of LE-PBMA/graphene 12 w%, and it was compared to that of pure LE-PBMA prepared by ATRP (atom transfer radical polymerization) method. When compared with those of PBMA prepared by free radical polymerization, the trend of depolymerization for LE-PBMA in the presence of graphene in the composite system decreased from 78% (by mol) up to 37% (by mol). The FT-IR, H-1- C-13-NMR and GC-MS data showed that depolymerization corresponding to monomer (benzyl methacrylate) was the most important product trapped at CRF (cold ring fraction) in the thermal degradation of composite.
Keywords: Thermal degradation; Composite; Poly(benzyl methacrylate); ATRP; Electrical properties